2017 8th International IEEE/EMBS Conference on Neural Engineering (NER) 2017
DOI: 10.1109/ner.2017.8008378
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting group performance in target-face recognition via collaborative brain-computer interfaces for surveillance applications

Abstract: Abstract-This paper presents a hybrid collaborative braincomputer interface (cBCI) to improve group-based recognition of target faces in crowded scenes recorded from surveillance cameras. The cBCI uses a combination of neural features extracted from EEG and response times to estimate the decision confidence of the users. Group decisions are then obtained by weighing individual responses according to these confidence estimates. Results obtained with 10 participants indicate that the proposed cBCI improves decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…As expected, BCI-assisted groups are significantly more accurate than equally-sized traditional groups based on standard majority for all group sizes -see "(a) vs (b)" column in Table 1. This confirms previous results obtained with this collaborative BCI both with the same set up (but using a combination of different neural features and reaction times) 40 , and in other visual-search experiments 39 . Moreover, ResNet-assisted groups were also significantly more accurate than traditional groups of only humans for all group sizes, as per "(a) vs (c)" column in Table 1.…”
Section: The Resnet Distinguishes Itself From the Crowdsupporting
confidence: 90%
See 3 more Smart Citations
“…As expected, BCI-assisted groups are significantly more accurate than equally-sized traditional groups based on standard majority for all group sizes -see "(a) vs (b)" column in Table 1. This confirms previous results obtained with this collaborative BCI both with the same set up (but using a combination of different neural features and reaction times) 40 , and in other visual-search experiments 39 . Moreover, ResNet-assisted groups were also significantly more accurate than traditional groups of only humans for all group sizes, as per "(a) vs (c)" column in Table 1.…”
Section: The Resnet Distinguishes Itself From the Crowdsupporting
confidence: 90%
“…More recently, we have used our hBCI to assist humans searching for a target face in a crowded, indoor environment 40 , which is of critical importance in many domains and is the application area considered also in this article. Once again, even in this real-world situation, groups of humans assisted by our hBCI were significantly more accurate than traditional groups based on standard majority or reported confidence 40 . While this is encouraging, with or without the assistance of an hBCI, even trained operators find this task hard and very fatiguing.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…We used confidence estimates to weigh individual decisions and make group decisions, which were significantly better than those of individuals and equally-sized groups using standard majority. Similar results were then obtained with more realistic tasks based on static images [4], [9], [12]. We also showed that cBCI confidence estimates were better calibrated than the confidence reported by participants after each decision [9].…”
Section: Introductionsupporting
confidence: 84%